Applying ethical climate theory in whistleblowing intentions study among employees in halal food companies: a protocol - Abd Rashid, Nur Rasyidah; Ahmad, Anis Najiha; Md Dahlal, Norazilawati; Abdullah, Moha Asri (IIUM Press, 2023)
Halal food fraud, such as fake Halal logos and adulteration, may happen due to irresponsible manufacturers seeking to maximise profit. Furthermore, Halal food fraud has been increasing over the years in Malaysia, and this issue needs to be considered since it is a major threat to Malaysia's reputation as an international Halal hub. One of the effective measures in reducing Halal food fraud is whistleblowing. In order to encourage whistleblowing, governments have established laws and policies to protect whistleblowers, but a lot of people are still unwilling to blow the whistle due to the retaliation that whistleblowers will face. Factors that may influence this ethical behaviour need to be studied. Therefore, the purpose of this article is to conceptually discuss potential factors (ethical climate types, organisation size, tenure, supervisor status, and religious obligation) that influence employees' intention to be involved in whistleblowing. A research model is proposed, followed by the developing of research hypotheses to test the model. In addition, the study's protocol (detailed plan) is later described. The theory of Ethical Climates will be used to guide this study. Data will be collected through convenience sampling by distributing self-administered questionnaires to 300 employees from Halal food companies in Malaysia. The collected data will be tested using Exploratory Factor Analysis (EFA) and Structural Equation Modelling-Partial Least Square (SEM-PLS). The findings from this study will help Halal food companies improve their whistleblowing practices. In addition, this study is useful for relevant policymakers to support whistleblowing practices.